ANALISIS STRUKTUR PEMBANGUNAN GEDUNG PERKULIAHAN FAKULTAS PERTANIAN UNIVERSITAS SRIWIJAYA - Rama Dwi Gantara, M. Merdi Rusmanto; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The construction of a safe, efficient, and technically compliant lecture building is essential to support academic activities in higher education institutions. This study aims to evaluate and analyze the structural performance of the Lecture Building for the Fisheries Department and the Department of Animal Technology and Industry at the Faculty of Agriculture, Sriwijaya University, in accordance with SNI 1726:2019 standards. The analysis was conducted using ETABS software version 22.4.0 to model the building structure. The results indicate that the building meets the criteria of SNI 1726:2019, with inter-story drifts of 10 mm in the X direction and 11 mm in the Y direction, both well below the allowable limit of 80 mm. Structural components such as the 25x40 cm footing with 6 D16 reinforcements, the 45x45 cm column K2 with 20 D19 reinforcements, and the 30x60 cm beam B1 with 10 D16 reinforcements are capable of supporting the factored loads without requiring reinforcement. Thus, the building structure is safe and complies with applicable technical standards based on the ETABS analysis.Keywords: ETABS, SNI 1726:2019, Building Structural Analysis, Dynamic Earthquake Analysis.